Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: • The Reality of Intellectual Compatibility Between Spouses and Its Relationship to Self-Efficacy Among Saudi Working Wives Ms. Huda Musa Hakami, Co-Prof. Najat Abdullah Malibari • The Cultural and Religious Impacts of Arabic Language on the State and Citizens: Bangladesh as a Case Study Co-Prof. Muhammad Abu Al-Kalam • The Impact of Happiness at Work on Improving Job Performance: An Applied Study in Government Agencies in the Kingdom of Saudi Arabia 2025 Mr. Khalid Awad Al-Enzi • Multiple Roles of Working Academic Women and their Relationship with Family Problems in Yemeni Universities: A Field Study at Aden University Dr. Saif Mohsen Abdulqawi • The Witness Shop in Damascus and Cairo (from the middle of the seventh century to the first quarter of tenth century AH) Mr. Mohammed Abdullah Zaouari • Self-awareness and its relationship to aggressive behavior among Palestinian adolescents Dr. Saeed Yousef Sweilim • Cricket as a Cultural Practice: An Ethnographic Study of the Pakistani Community in Tabuk Asst-Prof. Mohammed Ali M. Al Moteb ,Prof. Mohsen Abdalrhman Mohsen Al-Mohsen • Egyptian-Israeli Relations after Operation Flood of Al-Aqsa (2023-2025): A Descriptive-Analytical Study of Political and Diplomatic Transformations Dr. Mohammed Haidar Alastal